The Incidence of Pollution Control Policies - Ian W.H. Parry; Hilary Sigman; Margaret Walls; Williams Roberton C. (Rutgers University, Department of Economics, 2005)
Economic evaluations of pollution control policies have traditionally focused on pure efficiency effects either a comparison of their economic costs and environmental benefits, or a comparison of their costs relative to those of alternative control policies (e.g., Cropper and Oates 1992, Morgenstern 1997, Hahn 2005). However, the distribution of policy costs and benefits across households and firms is receiving increasing attention among researchers and policymakers.1 One reason is concern about whether a policy is ?fair? or not. Another is political feasibility a policy justifiable on efficiency grounds may be impractical if it imposes a disproportionate burden on a politically influential group. Often the two are critically related; for example, political opposition to higher fuel taxes, carbon taxes, or other emissions taxes in the United States is frequently based on the claim that such taxes fall most heavily on low-income groups. The purpose of this paper is to summarize what is actually known, and not known, about the incidence of benefits and costs from pollution taxes, and alternative emissions control measures, across household income groups.
Keywords: 330; Umweltpolitik; Umweltschutz; Verteilungswirkung; Emissionsrechte; Wirtschaftspolitische Wirkungsanalyse; USA